Highly Enantioselective Kinetic Resolution of Axially Chiral BINAM Derivatives Catalyzed by a Brønsted Acid1. Issue 14 (3rd March 2014) - Cheng, Dao‐Juan; Yan, Liang; Tian, Shi‐Kai; Wu, Ming‐Yue; Wang, Lu‐Xin; Fan, Zi‐Li; Zheng, Sheng‐Cai; Liu, Xin‐Yuan; Tan, Bin
Abstract A highly efficient strategy for the kinetic resolution of axially chiral BINAM derivatives involving a chiral Brønsted acid‐catalyzed imine formation and transfer hydrogenation cascade process was developed. The kinetic resolution provides a convenient route to chiral BINAM derivatives in high yields with excellent enantioselectivities.